12. Effectiveness of Jatropha Sap Oinment 10% (Jatropha curcas Linn.) and Gentamicin Ointment 0.1% on Combustion Injury II Healing on Mice Skin (Mus musculus) (EFEKTIVITAS SALEP GETAH JARAK PAGAR 10% (Jatrophacurcas Linn.) DAN GENTAMISIN 0,1% TERHADAP PERCEPATAN PENYEMBUHAN LUKA BAKAR DERAJAT II PADA KULIT MENCIT (Mus musculus)) - Rodi Jasmadi (Jurnal Medika Veterinaria, 2016)
This research was aimed to determine the effectiveness of second degree combustion wound healing after the administration of Jatropha (Jatropha curcas Linn.) sap oinment 10% and Gentamicin ointment 0.1% on mice skin (Mus musculus). This research used 12 mice divided into 3 treatment groups: yellow vaseline lubrication (K0), jatropha sap oinment 10% (KI), and ointment Gentamicin 0.1% (KII). The parameter measured in this study was healing time (day) based on wound not visible/healed (diameter length=0 cm). Data of wound healing were analyzed using analysis of variance (Anova) and continued with least significant difference test. The time of wound healing on P0, P1, and P2 was 22.25, 17.75, and 20.25 days (P0.01). In conclusion, sap of jatropha oinment 10% is potensial to accelerate the combustion injury II healing process in mice. ____________________________________________________________________________________________________________________ Key words: wound, yellow vaseline, jarak pagar secretion 10%, gentamicin 0.1 %